Superomniphilic Poly(glycerol sebacate)–Poly(l‐lactic acid) Electrospun Membranes for Oil Spill Remediation. Issue 20 (24th July 2017) - Yan, Yi; Sencadas, Vitor; Zhang, Jiangshan; Wei, Dongbin; Jiang, Zhengyi
Abstract: Superomniphilic materials are defined as materials that can uptake both water and oil‐like liquids. In this study, a facile method to prepare a superomniphilic and biodegradable core–shell structure of poly(glycerol sebacate) (PGS) and poly(l ‐lactic acid) (PLLA) is reported. The developed method immobilizes the PGS polymer onto the surface of the PLLA electrospun fibers, increasing the presence of hydroxyl groups on the surface of the membranes. The sample with 25 wt% PGS can uptake polar and apolar solvents, and presents a superhydrophilic behavior. The PGS‐PLLA composite is reusable up to 10 cycles of solvent (water of organic solvents) absorption with a separation efficiency of 99.5%, and its general appearance resembles the first absorption/compression cycle. Finally, this work presents a novel biodegradable polymeric blend membrane with superomniphilic properties, produced by a scalable process, which could be easily implemented to fight against environmental disasters such as large area oil spills. Abstract : Large area oil spill is becoming an increasing threat to environment. Superomniphilic electrospun membranes with core–shell structure are prepared by a scalable process. Presented with the capability of selectively absorbing oil, the membrane can be reused for at least 10 cycles with a separation efficiency of 99.5% and with consistent absorbing performance.